Various Occurrence Mechanisms of Large Acceleration over 20 m/s2 and Its Suitability in Design Use - Kamagata, Shuichi; Takewaki, Izuru (Frontiers in Built Environment, 2018)
Three amplification mechanisms of large accelerations over 20m/s2 are related to various non-liner behaviors and explained by using the non-stationary Fourier spectra. The frequencies of dominant components are compared with the natural frequencies with the ratios (1:3:5:7) of a shear-spring model of the underground soil. Thus, one of the amplification mechanisms is supposed to result from the natural modes in the underground soil. Furthermore the similarity of pulse waves between MYG012 (EW) and AKTH04 (EW) is pointed out in the non-stationary Fourier spectra and the double-integrated displacement profiles. The pulse waves are identified by the Ricker wavelet. This amplification mechanism is supposed to be caused by the collision between the observation house and the side soil. The modulation of dominant component is also detected in the high frequency range. The shear strain of AKTH04 is calculated using the relative displacement profiles between the surface and the borehole. The peak shear strain is fitted to the G-γ relation and the deterioration ratio of shear stiffness is evaluated. The third amplification mechanism is related to the change of depth of isolated surface soil. The depth of the isolated surface soil is evaluated from the deterioration area shallower than 20m. It is pointed out finally that the seismic records at the ground surface are unsuitable for the database of seismic design wave.